First person - Tylor Lewis (The Company of Biologists, 2022)
First Person is a series of interviews with the first authors of a selection of papers published in Disease Models & Mechanisms, helping researchers promote themselves alongside their papers. Tylor Lewis is first author on ' Microvesicle release from inner segments of healthy photoreceptors is a conserved phenomenon in mammalian species', published in DMM. Tylor is a postdoc in the lab of Vadim Arshavsky at Duke University Medical Center, Durham, NC, USA, investigating the biology of the visual system and the pathophysiological mechanisms of retinal disease.